2021
DOI: 10.1097/aud.0000000000001035
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of the Electrically Stimulated Auditory Nerve to Amplitude Modulation Cues Declines With Advanced Age

Abstract: Objectives: This study aimed to investigate effects of aging and duration of deafness on sensitivity of the auditory nerve (AN) to amplitude modulation (AM) cues delivered using trains of biphasic pulses in adult cochlear implant (CI) users. Design: There were 21 postlingually deaf adult CI users who participated in this study. All study participants used a Cochlear Nucleus device with a full electrode array insertion in the test ear. The stimulus was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…As a result, different definitions and quantifying methods have been used to evaluate duration of deafness in different studies or even in different datasets collected for the same study (e.g., Blamey et al 1996). In our previous study (Riggs et al 2021), we attempted to quantify duration of deafness using three different approaches in the same group of CI users. Specifically, the self-reported duration of deafness was defined as the interval between the time points, when looking back, the participants felt a CI would have been an appropriate option for their hearing loss and the time of CI surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, different definitions and quantifying methods have been used to evaluate duration of deafness in different studies or even in different datasets collected for the same study (e.g., Blamey et al 1996). In our previous study (Riggs et al 2021), we attempted to quantify duration of deafness using three different approaches in the same group of CI users. Specifically, the self-reported duration of deafness was defined as the interval between the time points, when looking back, the participants felt a CI would have been an appropriate option for their hearing loss and the time of CI surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the clinician-defined duration of deafness was measured as the interval between when the participant's audiologist or otologist initially recommended the CI as a treatment option and the time of CI surgery. There were 16 participants included in the present study who also participated in the study of Riggs et al (2021). These participants were A003, A004, A006, A007, A008, A009, A011, A019, A020, A024, A029, A030, A032, A034, A035, and A041.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…One potential limitation of the present study is the inability to control for factors other than age at testing that have been shown to affect the ENI, such as etiology of hearing loss (Jahn & Arenberg 2020a; Jahn et al 2020) and duration of deafness (Nadol et al 1989; Kim et al 2013). Unfortunately, the duration of deafness cannot be reliably measured in adult CI users (Riggs et al 2021), and etiologies of many CI users cannot be identified. Therefore, these potentially confounding factors could not be controlled in the present study.…”
Section: Discussionmentioning
confidence: 99%